Earliest stage treatment of actinic keratosis with imiquimod 3.75% cream: Two case reports—Perspective for non melanoma skin cancer prevention. Issue 4 (30th June 2020) - Kopera, Daisy
Abstract: Imiquimod 3.75% cream is licensed for the treatment of actinic keratosis (AK). Two case reports on the treatment of facial UV‐exposed skin shall open the discussion if subclinical AKs can be detected by the use of imiquimod cream in UV‐exposed areas even if no lesions can be found clinically. A 87‐year old female showing small scaly AK lesions on her right cheek was treated with imiquimod 3.75% cream. A 59‐year old female without obvious clinical signs of UV‐damage on the face experimentally applied imiquimod 3.75% cream twice daily on the entire face for 2 weeks. In the 87‐year old, inflammatory reaction developed from day 3 onward and showed field cancerization, the lesions healed without scarring. In the 59‐year old at the end of the treatment phase, distinct signs of inflammation appeared, then taking 2 weeks for healing without sequalae. These results open the discussion if the use of imiquimod 3.75% cream could be recommended preventively in UV‐exposed skin areas to obviate a later development of AKs/squamous cell carcinoma/nonmelanoma skin cancer.